COMMUNITY RESPONSIVENESS TO THE FEASIBILITY OF THE YOGYAKARTA-SEMARANG RAILROAD VIA MAGELANG REACTIVATION PROGRAM - Khusnaya, Amalia; Sulistiyani, Ambar Teguh; Anggalini, Titis Dewi (Universitas Negeri Yogyakarta, 2021)
This study aims to assess the feasibility of the Jogjakarta-Semarang railroad reactivation program via Magelang. The research method used is a quantitative method through surveys and qualitative methods using interview techniques. Feasibility is assessed from 4 aspects, namely aspects of need, technical, management and law, and social aspects. The survey results were processed using Microsoft Excel 2010 applications. Qualitative analysis was strengthened by data triangulation techniques. The findings of this study indicate that the Jogjakarta-Semarang railroad reactivation program via Magelang is feasible in two aspects, needs and management and law. While it is considered not feasible according to technical and social aspects. However, reactivation programs should continue to be carried out because future regional developments require alternative modes of transportation. To overcome this, researchers recommend a middle ground, namely 1) Partial reactivation; 2) Development of elevated lines; 3) Policy of swap with additional compensation. Generally, commuters responds positively to railroad reactivation programs, but if the railroad tracks hit a functional building that exists, then commuters have several considerations.